2013
DOI: 10.1007/s10072-013-1360-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of behavioral therapies in adult and adolescent patients with chronic migraine

Abstract: Patients with chronic migraine (CM) headaches present some of the most difficult treatment challenges for headache practitioners. Attention to psychological and behavioral issues become significant treatment considerations as the frequency of a patient's headaches increases, there is increased disability secondary to headaches, and/or there is inadequate response to usually effective treatment. Recent research has identified a variety of risk factors (including medication overuse) that appear to be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Psychological factors are well known to influence the development and maintenance of chronic pain 18; 27 , including among youth experiencing chronic headache 19; 23; 52 . In the current study we examined whether self-efficacy, a demonstrated influential cognitive appraisal, may be a protective factor that can mitigate the influence of fear on negative functional outcomes (e.g., disability, depression) as has been observed in adult pain patients 53; 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Psychological factors are well known to influence the development and maintenance of chronic pain 18; 27 , including among youth experiencing chronic headache 19; 23; 52 . In the current study we examined whether self-efficacy, a demonstrated influential cognitive appraisal, may be a protective factor that can mitigate the influence of fear on negative functional outcomes (e.g., disability, depression) as has been observed in adult pain patients 53; 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-pharmacological therapy, in particular behavioral strategies seem to be as effective as pharmacological treatment for headache management ( 3 , 58 , 59 ).…”
Section: The Role Of Metacognition Cognitive Behavioral Therapy (Cbtmentioning
confidence: 99%
“…Being aware of factors that precipitate or aggravate CM should allow patients to progressively modulate the frequency and duration of their attacks 63. Cognitive-behavioral therapy may also be indicated to assess compliance to preventive medication and to assess modifiable risk factors for CM 62. Other reasons that cause CM patients to seek cognitive-behavioral therapy and other nonpharmacological treatments include poor tolerance and low response to preventive medication, history of overuse of medication, pregnancy, stress, and deficient stress/pain coping strategies 62…”
Section: Management Of Chronic Migrainementioning
confidence: 99%